Does Religion Matter to Owner-Manager Agency Costs? Evidence from China - Du, Xingqiang (Journal of business ethics, 2013)
In China, Buddhism and Taoism are two major religions. Using a sample of 10,363 firm-year observations from the Chinese stock market for the period of 2001–2010, I provide strong and robust evidence that religion (i.e., Buddhism and Taoism on the whole) is significantly negatively associated with owner-manager agency costs. In particular, using firm-level religion data measured by the number of religious sites within a radius of certain distance around a listed firm’s registered address, I find that religion is significantly negatively (positively) associated with expense ratio (asset utilization ratio), the positive (reverse) proxy for owner-manager agency costs. This finding is consistent with the following view: religiosity has remarkable effects on the way how an individual thinks and behaves, and thereof can curb managers from unethical business practices. Moreover, my findings suggest that the negative association between religion and owner-manager agency costs is attenuated for firms with strong external monitoring mechanisms such as higher Marketization and high-quality auditors. Furthermore, after separating Buddhism from Taoism, my finding indicates that above conclusions are only available for Buddhism, suggesting that different religions may have asymmetric influence on owner-manager agency costs. Above results are robust to various measures of religiosity and a variety of robustness checks.